Cross-Country Experience with Restructuring of Sovereign Debt and Restoring Debt Sustainability. (Policy Papers; Policy Paper ;, 2006)
The paper is organized as follows: Section II provides a cross-country overview of the economic conditions, including the composition of sovereign debt and its dynamics prevailing prior to the debt operations, and a discussion of the scope and outcomes-in terms of the debt relief provided by creditors-of the debt restructurings. Section III analyzes the debt profile, liquidity position, DSAs and accompanying stress tests, and an EWS to assess whether debt sustainability has been restored in each country case. Conclusions are set out in Section IV.